Evaluation of Pretreatments for Inhibiting Bromate Formation During Ozonation - Andersen, Henrik Rasmus; Antoniou, Maria G. (My University, 2012)
This study compared several pretreatment methods for inhibiting BrO−3 formation during ozonation of tap water, fromtheDTU (Technical University of Denmark) campus, including H2O2 addition (peroxone), pH depression, and NH+4 and Cl2/NH+4 addition. At the same time, the inhibition of atrazine and carbamazepine removal was evaluated for each pretreatment. The required delivered O3 dose to achieve 90% removal of atrazine in the tap water from the DTU campus was 3.5 mg/L, which produced 130–170μg/L BrO−3 . Peroxone did not reduce the required O3 dose for contaminant removal; however, it limited BrO−3 formation to below the drinking water limit of 10μg/L. Depression of solution pH to 6.0, reduced BrO−3 formation to half, but it was still well above the water limit. Pretreatment with NH+4 also reduced BrO−3 formation by approximately 50%, though it reduced atrazine degradation to 65%. Pretreatment with Cl2/NH+4 reduced BrO−3 formation close to the 10μg/L limit; however, atrazine removal did not exceed 75%. Carbamazepine was completely removed under all the tested experimental conditions with the 3.5 mg/L O3 dose.
Keywords: Bromate; Chlorine; Ozone; Carbamazepine; Ammonia